1993
DOI: 10.1111/j.1476-5381.1993.tb13933.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression of primary afferent‐evoked responses by GR71251 in the isolated spinal cord of the neonatal rat

Abstract: 1 The pharmacological profile of GR71251, a new tachykinin receptor antagonist, and its effect on the responses evoked by stimulation of primary afferent fibres were studied in isolated spinal cord preparations of neonatal rats. Potential changes were recorded extracellularly from a lumbar ventral root (L3-L5).2 Bath-application of substance P (SP), neurokinin A (NKA) and neurokinin B (NKB) at 0.01-3 AM to the spinal cord induced depolarization of the ventral root in normal artificial cerebrospinal fluid (CSF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
6
14
0
Order By: Relevance
“…The depressant effects of GR71251 and RP67580 on the descending fibre-evoked slow depolarization of motoneurones are therefore probably due to their blocking actions on tachykinin NK1 receptors. The contributions of NK2 and NK3 tachykinin receptors to the tachykininergic slow EPSP may be negligible, because our previous studies have shown that both NK2 and NK3 agonists had little or no depolarizing actions on neonatal rat spinal motoneurones (Yanagisawa & Otsuka, 1990;Guo et at. 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The depressant effects of GR71251 and RP67580 on the descending fibre-evoked slow depolarization of motoneurones are therefore probably due to their blocking actions on tachykinin NK1 receptors. The contributions of NK2 and NK3 tachykinin receptors to the tachykininergic slow EPSP may be negligible, because our previous studies have shown that both NK2 and NK3 agonists had little or no depolarizing actions on neonatal rat spinal motoneurones (Yanagisawa & Otsuka, 1990;Guo et at. 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is likely that the tachykinins responsible for the slow EPSP are mainly contained in serotonergic descending fibres. Guo et al (1993) and Hosoki et al (1994) examined the pharmacological profiles of GR71251 and RP67580 in the neonatal rat spinal cord and showed that they were specific tachykinin NK1 receptor antagonists. Furthermore, RP68651, the inactive enantiomer of RP67580, had no effect on the descending fibre-evoked slow VRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a lumbar (L3 ± 5) dorsal root was stimulated every 2 min with a single square pulse of 100 ms duration at 30 ± 40 V in an isolated spinal cord preparation, a monosynaptic re¯ex was elicited in the ipsilateral ventral root of the same segment and was followed by a slow VRP lasting about 30 s. Previous studies showed that the slow VRP was depressed by various tachykinin NK 1 receptor antagonists (Akagi et al, 1985;Guo et al, 1993), suggesting the involvement of SP and neurokinin A in the slow VRP. When monosynaptic re¯exes and slow VRPs became stable after about 1 h of perfusion with normal arti®cial CSF, wortmannin at 1 mM was added to the perfusion medium.…”
Section: Electrophysiological Experimentsmentioning
confidence: 99%
“…This preparation enables us to obtain stable extracellular recording from ventral roots and thus to carry out detailed pharmacological analyses of both responses to nerve stimulation and responses to exogenously applied agents. Activation of primary afferent fibres by either electrical stimulation at C-fibre strength or peripheral noxious stimulation evokes a depolarization of a slow time course in ventral roots and this depolarization is markedly depressed by tachykinin antagonists as well as opioid agonists (Akagi et al, 1985;Otsuka & Yanagisawa, 1988;Nussbaumer et al, 1989;Yanagisawa et al, 1992;Guo et al, 1993;Hosoki et al, 1994). These and other lines of evidence suggest that this depolarization, hereafter referred to as the slow ventral root potential (VRP), represents a C-fibre-evoked nociceptive response in which tachykininergic primary afferents are involved (Otsuka & Yanagisawa, 1987).…”
Section: Introductionmentioning
confidence: 99%